2014
DOI: 10.12740/pp/21684
|View full text |Cite
|
Sign up to set email alerts
|

The effect of lithium on thyroid function in patients with bipolar disorder.

Abstract: Począwszy od roku 1963 stosowanie litu stanowi najbardziej udokumentowany sposób postępowania długoterminowego w chorobie afektywnej dwubiegunowej (ChAD), zarówno dla zapobiegania epizodom depresyjnym, jak i maniakalnym, a także zmniejszania ryzyka samobójstwa. W ChAD czynność gruczołu tarczowego i osi podwzgórze-przysadka-tarczyca (PPT) ma istotne znaczenie dla patofizjologii, przebiegu klinicznego i leczenia tej choroby. Wpływ litu na gruczoł tarczowy stanowi jedno z najważniejszych działań niepożądanych dł… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 55 publications
0
10
1
2
Order By: Relevance
“…Pathogenesis of Graves’ disease (GD). * viral and bacterial infections, iodine, stress, medications, external radiation, radioactive iodine, toxins, selenium and vitamin D3 deficiency, lymphopenia, smoking, CD8+ T lymphocyte deficiency [5,6,7,8,9,10,11]. …”
Section: Figurementioning
confidence: 99%
“…Pathogenesis of Graves’ disease (GD). * viral and bacterial infections, iodine, stress, medications, external radiation, radioactive iodine, toxins, selenium and vitamin D3 deficiency, lymphopenia, smoking, CD8+ T lymphocyte deficiency [5,6,7,8,9,10,11]. …”
Section: Figurementioning
confidence: 99%
“…In bipolar disorder, the thyroid function should be examined in the context of a role of the thyroid gland and the hypothalamic-pituitary-thyroid axis in the pathophysiology of this illness. The most frequent side effects associated with longitudinal lithium administration are goiter and hypothyroidism (Kraszewska et al, 2014 ). We studied 137 patients with bipolar disorder, including 98 subjects (30 male, 68 female) receiving lithium for at least 3 years (mean 19 + 10 years) and 39 subjects (12 male, 27 female) never receiving lithium, The groups were matched for age and the duration of illness.…”
Section: The Adverse Effects Of Long-term Lithium Treatment and Theirmentioning
confidence: 99%
“…Previous study found that hypothalamic-pituitary-thyroid (HPT) axis abnormalities play an important role in the pathophysiology and treatment of BD [18]. Researchers also found that hyperthyroidism may increase the risk of developing BD [19].…”
Section: Introductionmentioning
confidence: 99%